Saccadic Impairments in Patients with the Norrbottnian Form of Gaucher’s Disease Type 3 - Blume, Josefine; Beniaminov, Stanislav; Kämpe Björkvall, Cecilia; Machaczka, Maciej; Svenningsson, Per (Frontiers in Neurology, 2017)
Background Chronic neuronopathic Gaucher’s disease type 3 (GD3) is relatively frequent in northern Sweden. Besides multiple other neurological symptoms, horizontal gaze palsy or oculomotor apraxia is common in GD3. Objective To characterize the saccades in patients with Norrbottnian GD3 with respect to their neurological and cognitive status using a computer-based eye-tracking technique. Methods Horizontal and vertical reflexive saccades as well as antisaccades of nine GD3 patients [4M/5F; 41.1 ± 11.0 years; modified severity scoring tool (mSST): 9.3 ± 5.4; Montreal Cognitive Assessment (MoCA): 24.0 ± 4.2] and age-matched controls were analyzed using EyeBrain T2, a head-mounted binocular eye tracker. Systematic clinical assessment included the mSST, a valid tool for monitoring the neurological progression in GD3 and MoCA. Results In Norrbottnian GD3 patients, gain, peak, and average velocity (107.5°/s ± 41.8 vs. 283.9°/s ± 17.0; p = 0.0009) of horizontal saccades were reduced compared to healthy controls (HCs). Regarding vertical saccades, only the average velocity of downward saccades was decreased (128.6°/s ± 63.4 vs. 244.1°/s ± 50.8; p = 0.004). Vertical and horizontal saccadic latencies were increased (294.3 ms ± 37.0 vs. 236.5 ms ± 22.4; p = 0.005) and the latency of horizontal reflexive saccades was correlated with the mSST score (R2 = 0.80; p = 0.003). The latency of antisaccades showed association to MoCA score (R2 = 0.70; p = 0.009). GD3 patients made more errors in the antisaccade task (41.5 ± 27.6% vs. 5.2 ± 5.8%; p = 0.005), and the error rate tended to correlate with the cognitive function measured in MoCA score (p = 0.06). Conclusion The mean age of 41 years of our GD3 cohort reflects the increased life expectancy of patients in the Norrbottnian area compared to other GD3 cohorts. Marked impairment of horizontal saccades was evident in all patients, whereas vertical saccades showed distinct impairment of downward velocity. Latency of reflexive saccades was associated with the severity of neurological symptoms. Increased latency and error rate in the antisaccade task were linked to cognitive impairment. The assessment of saccades provides markers for neurological and neuropsychological involvement in Norrbottnian GD3.